The Impact of Nutritional Education Interventions on Maternal Knowledge, Self-Monitoring, and Stunting Prevention among Children Under Five: A Literature Review - Lindawati Lindawati; Herry Susanto; Sri Wahyuni; Nopi Nur Khasanah (Indonesian Journal of Global Health Research, 2026)
Stunting remains a major chronic nutritional problem among children under five in developing countries, including Indonesia. Low maternal knowledge and limited ability to monitor child nutrition are key contributing factors. Nutritional education interventions play an essential role in improving nutrition literacy, self-monitoring capacity, and stunting prevention practices among mothers of young children. This literature review aims to analyze the impact of nutritional education interventions on enhancing maternal knowledge and self-monitoring skills, as well as their effectiveness in preventing stunting among children under five, based on quasi-experimental and randomized controlled trial (RCT) studies. The review process followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Articles were retrieved from PubMed, ScienceDirect, Google Scholar, and Garuda (Garba Rujukan Digital) databases using the keywords: nutrition education, maternal knowledge, self-monitoring, stunting prevention, and children under five. The publication range included studies from 2020 to 2025. Out of 312 initially identified articles, duplicates were removed, and eligibility was assessed based on inclusion and exclusion criteria, resulting in 12 studies selected for in-depth analysis. Methodological quality was appraised using the Joanna Briggs Institute (JBI) Critical Appraisal Tools. Inclusion criteria comprised: (1) quasi-experimental or RCT study design; (2) population of mothers with children under five; (3) interventions involving nutrition education, health promotion, or maternal empowerment programs related to child nutrition; (4) open-access full-text availability; and (5) publications in English or Indonesian. Exclusion criteria included review articles, case reports, descriptive studies without intervention, populations other than mothers, studies not assessing outcomes related to knowledge, behavior, or child nutritional status, and articles lacking peer review or full-text access. Analysis of the 12 selected studies revealed that nutritional education interventions consistently improved maternal knowledge, feeding behavior, and self-monitoring practices while reducing the prevalence of stunting. Interventions combining education with maternal empowerment and community-based mentoring demonstrated greater effectiveness compared to education-only approaches. Overall, nutritional education interventions are effective in improving maternal knowledge and self-monitoring skills, contributing to stunting prevention among children under five. Continuous, community-based education integrated into primary health services is recommended to strengthen maternal roles and enhance the effectiveness of stunting prevention programs.